Hubungan Stres Dan Riwayat Keluarga Dengan Kejadian Dismenore Pada Mahasiswa Di Akademi Kebidanan Bina Banua Husada Banjarbaru Tahun 2016 - Siska Dhewi; Fakultas Kesehatan Masyarakat UNISKA (Jurnal Kesehatan Indonesia, 2016)
According to the Adolescent Reproductive Health Survey Indonesia (SKKI, 2007), the teenagers were men and unmarried women with an age limit covering 15-24 years. In the period of rapid change in the physical, mental and social. Menstruation or we are familiar with menstruation is the incidence of naturally occurring in normal women. This occurs because the release layer endumetrium uterus. Dysmenorrhea is one complaint most common gynecological in women and experience the sensation of discomfort during menstruation, discomfort in the lower abdomen, back down even to the thighs. Study aims the team to analyze the relationship between stress and portfolio families with incidence of dysmenorrheal in Midwifery Academy student at Bina Banua Husada Banjarbaru 2016. Type of research is an analytic cross sectional study. The research object is the third semester student, the population of 79 respondents with a total sampling technique. The research instruments were questionnaires to collect data stress level and family history of dysmenorrhea student about the incident. The data is then processed and analyzed with chi square test, for a family history showed 0,029 a means that there is a relationship between the variables of family status with the incidence of dysmenorrheal and stress variables with the results of 0,012 a means that there is a relationship of stress with the incidence of dysmenorrheal in mahasiswi Midwifery Academy Bina Banua Husada Banjarbaru 2016.